Antinuclear antibodies in the relatives and spouses of patients with systemic sclerosis. Issue 10 (October 1986) - Maddison, P J; Skinner, R P; Pereira, R S; Black, C M; Ansell, B M; Jayson, M I; Rowell, N R; Welsh, K I
Abstract : The families of 65 patients with systemic sclerosis were examined clinically and serum samples from each subject were tested for antinuclear antibodies (ANA) by immunofluorescence on HEp2 cells and for precipitating antibodies to soluble cellular antigens including Scl-70. Of 217 blood relatives, 58 (27%) had ANA (42 speckled, 13 nucleolar, one centromere, two homogeneous); 22 (10%) had precipitins, one anti-Scl-70, one anti-PM-Scl, one anti-nRNP, two anti-Ro(SSA), the remainder unidentified). Family members tended to share ANA patterns. Of 38 spouses, nine (24%) had ANA (all speckled) and two showed unidentified precipitins. This compares with an incidence of ANA and precipitins in a control population of 8% and 1% respectively. Antibodies were more common in female than male relatives (particularly in mothers and sisters of probands). Twenty one of the 58 family members with ANA had clinical features of connective tissue disease; the remainder were asymptomatic. The presence of genetic factors influencing autoimmunity is suggested by the incidence of autoantibodies in first degree relatives. Similar observations in spouses, however, indicate that environmental factors may also have a role in these immune abnormalities.